The Role of Social Emotional Health on Academic Achievement of College Students - Yansaputri, Intan Shabrina; Wijaya, Hariz Enggar (Universitas Muhammadiyah Metro, 2017)
Research on positive psychology has widely grown since its emergence. The strength of the human becomes a key point of positive psychology to explore, such as self-efficacy, optimism, self-control, etc. This research applied positive psychology to evaluate the role of social-emotional health on the academic achievement of college students. There were 107 first year psychology students of the Islamic University of Indonesia participating this study. Data were collected using the Social Emotional Health Survey System (SEHS-S) developed by Jones, You, and Furlong (2012) and Grade Point Average (GPA) of students. Data analysis showed that Social Emotional Health was correlated with GPA. Three domains within Social Emotional Health Survey System such as belief in self, emotional competence, and engaged living were positively correlated with GPA. However, belief in others does not correlate with GPA.